Impact of elevated HbA1c on long-term mortality in patients presenting with acute myocardial infarction in daily clinical practice: insights from a 'real world' prospective registry of the Zwolle Myocardial Infarction Study Group. Issue 6 (1st September 2020) - Hermanides, Renicus S; Kennedy, Mark W; Kedhi, Elvin; van Dijk, Peter R; Timmer, Jorik R; Ottervanger, Jan Paul; Dambrink, Jan-Henk; Gosselink, AT Marcel; Roolvink, Vincent; Miedema, Kor; Slingerland, Robbert J; Koopmans, Petra; et al.
Abstract : Background: Long-term clinical outcome is less well known in up to presentation persons unknown with diabetes mellitus who present with acute myocardial infarction and elevated glycosylated haemoglobin (HbA1c) levels on admission. We aimed to study the prognostic impact of deranged HbA1c at presentation on long-term mortality in patients not known with diabetes, presenting with acute myocardial infarction. Methods: A single-centre, large, prospective observational study in patients with and without known diabetes admitted to our hospital for ST-segment elevation myocardial infarction (STEMI) and non-STEMI. Newly diagnosed diabetes mellitus was defined as HbA1c of 48 mmol/l or greater and pre-diabetes mellitus was defined as HbA1c between 39 and 47 mmol/l. The primary endpoint was all-cause mortality at short (30 days) and long-term (median 52 months) follow-up. Results: Out of 7900 acute myocardial infarction patients studied, 1314 patients (17%) were known diabetes patients. Of the 6586 patients without known diabetes, 3977 (60%) had no diabetes, 2259 (34%) had pre-diabetes and 350 (5%) had newly diagnosed diabetes based on HbA1c on admission. Both short-term (3.9% vs. 7.4% vs. 6.0%, p< 0.001) and long-term mortality (19% vs. 26% vs. 35%, p< 0.001) for both pre-diabetes patients as well as newly diagnosed diabetes patients was poor and comparable to known diabetes patients. After multivariate analysis, newly diagnosed diabetes was independently associated with long-term mortality (hazard ratio 1.72, 95% confidence interval 1.27–2.34, P =0.001). Conclusions: In the largest study to date, newly diagnosed or pre-diabetes was present in 33% of acute myocardial infarction patients and was associated with poor long-term clinical outcome. Newly diagnosed diabetes (HbA1c ⩾48 mmol/mol) is an independent predictor of long-term mortality. More attention to early detection of diabetic status and initiation of blood glucose-lowering treatment is necessary.